Life-course blood pressure trajectories and incident diabetes: A longitudinal cohort in a Chinese population - Liu, Ying; Chen, Xiaohong; Li, Chunxia; Fan, Bingbing; Lv, Jiali; Qu, Yanlin; Cai, Yongjiang; Zhang, Tao (Frontiers in Endocrinology, 2022)
Background: Blood pressure levels are correlated with diabetes among middle-aged or older adults. However, longitudinal trajectories of blood pressure during young adulthood and their impact on diabetes has been understudied. Methods: The longitudinal cohort consisted of 4,625 adults who had blood pressure and body mass index (BMI) repeatedly measured 5-9 times during 18-60 years. Distinct systolic blood pressure (SBP) trajectories were identified by group-based trajectory model. Logistic regression analyses were used to investigate the association between trajectory patterns or quartiles of area under the curve values of SBP trajectories and incident diabetes, respectively. Results: Four distinct trajectory groups were identified for SBP: normotensive-stable (n=761, 16.5%), prehypertension-stable (n=2,381, 51.5%), stage I hypertension-increasing (n=1,231, 26.6%) and stage II hypertension-increasing (n=251, 5.4%). Compared with subjects who remained SBP <120 mmHg in the normotensive-stable group, individuals in the prehypertension-stable trajectory exhibited normal SBP range (<140 mmHg), they still had a significantly higher risk of diabetes (adjusted OR=1.82, P=0.029). Individuals had a greater risk of diabetes in the stage I hypertension-increasing group (adjusted OR=2.31, P=0.006) and the highest risk in the stage II hypertension-increasing group (adjusted OR=3.91, P<0.001) relative to the normotensive-stable group. Furthermore, compared with the first quartile, adjusted ORs (95% CIs) of the fourth quartile of SBP incremental and total AUC were 2.50 (1.61-3.97) and 1.82 (1.15-2.94), respectively. Conclusions: Long-term SBP trajectory is a significant predictor for incident diabetes which is independent of baseline SBP and body weight. Attaching importance to maintain optimal blood pressure levels and control changing slopes of SBP for preventing diabetes.